Research on the synthesis of TiO2-SiO2 nanoparticles for anti-bacterial coating application - Dang, Khoi Nguyen; Bui, Van Cuong; Le, Hai Khoa; Pham, Thi Lan; Tran, Dai Lam (Communications in Physics, 2023)
TiO2 has a strong photocatalytic activity, which can oxidize and decompose impurities on surfaces and in the air. Therefore, TiO2 is used as an additive for the self-cleaning coating and paint industry. In this work, SiO2 is used in the TiO2/SiO2 mixture as the nucleus to homogenize the dispersion components. TiO2 and SiO2 nanoparticles are synthesized by sol-gel method combined with ultrasound that suits for the size range of 10-30 nm. The nano mixture is added to two green paint samples as Green Lable Paint EXT (exterior wall paint) and Green Lable Paint INT (interior wall paint) to replace antibacterial agents in paint formulations. In results, two paint samples showed antibacterial capability in accordance with ASTM D2574-06 for antibacterial paints.